A fuzzy-tuned genetic algorithm for optimal reconfigurations of radial distribution network - Sahoo, N. C.; Ranjan, R.; Prasad, K.; Chaturvedi, A. (JOHN WILEY & SONS LTD, 2007)
A large amount of power can be saved by optimal reconfiguration of radial distribution systems (RDS). Moreover, by transferring loads from the strongly loaded feeders to the lightly loaded ones, the reconfiguration of RDS can also achieve balancing of feeder loads and alleviate overload conditions. This paper presents a new approach for optimal reconfiguration of RDS based on a fuzzy-tuned genetic algorithm by minimizing real power loss and improving loading pattern of the feeder. The proposed algorithm overcomes the combinatorial nature of the reconfiguration problem and deals with the optimization of a non-linear, non-continuous objective function. The main features of the proposed genetic approach for network reconfiguration are: preserving radial property of the network without islanding any load point by an elegant coding scheme and an efficient convergence characteristic attributed to tuned mutation using fuzzy logic. The proposed algorithm is tested for seven case studies on a 69-bus RDS. Copyright (c) 2006 John Wiley & Sons, Ltd.